1983
DOI: 10.1073/pnas.80.19.5965
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of Moloney murine leukemia virus mutants unable to synthesize glycosylated gag polyprotein.

Abstract: Retroviruses contain three genes for replication: gag, pol, and env, which encode polyprotein precursors for the internal capsid proteins, reverse transcriptase, and envelope glycoprotein, respectively (1). Murine leukemia virus (MuLV) differs from most other retroviruses in that it encodes two different pathways for gag gene expression (2). These two pathways begin with two independent translation products, gPr80gag and Pr65ag. Pr65gag is processed by proteolytic cleavage to yield the internal capsid proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 29 publications
4
68
0
Order By: Relevance
“…Glyco-Gag has long been known to be important for MLVinduced pathogenesis, and its abrogation leads to decreased virus replication and pathogenesis in vivo (4,(9)(10)(11)(12). However, previous studies carried out primarily in murine fibroblast lines such as NIH 3T3 that do not express APOBEC3 suggested that glyco-Gag was dispensable for in vitro infection.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Glyco-Gag has long been known to be important for MLVinduced pathogenesis, and its abrogation leads to decreased virus replication and pathogenesis in vivo (4,(9)(10)(11)(12). However, previous studies carried out primarily in murine fibroblast lines such as NIH 3T3 that do not express APOBEC3 suggested that glyco-Gag was dispensable for in vitro infection.…”
Section: Discussionmentioning
confidence: 88%
“…To determine whether this was also the case for M-MLV, we infected C57BL/6, BALB/c, and APOBEC3 KO pups with WT and glyco-Gag mutant M-MLV; the APOBEC3 null allele is present on the BL/6 background (26). The mutant virus has a stop codon in the gPr80Gag reading frame (UAU to UAG) at nt 608, 12 nt 5′ of the normal Gag AUG (9). BL/6 mice infected with the glyco-Gag mutant virus showed significantly lower levels of infectious virus in spleens and thymi (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…gPr80 gag 's is conserved among gammaretroviruses, but its mechanism of action has been elusive. MuLVs mutant in gPr80 gag are replication-competent with minor reductions in infectivity in vitro (6). However, when infected into mice, there is strong in vivo selection for recovery of gPr80 gag expression (7)(8)(9).…”
mentioning
confidence: 99%